Do developmental orthopaedic disorders influence future jumping performances in Warmblood stallions?. (24th January 2013) - Verwilghen, D. R.; Janssens, S.; Busoni, V.; Pille, F.; Johnston, C.; Serteyn, D.
Summary Reasons for performing the study Few reports are available on the relationship between developmental orthopaedic diseases (DOD) and future performances in Warmblood horses. Objectives To investigate the relationship between performance and the presence of DOD lesions. Methods Records of Warmblood stallions for which radiographic and performance data were available were collected. Showjumping performances were expressed as scores derived from the final ranking of horses in each competition. These scores are available in an established performance database. The relationship between radiographic findings and both performance scores and number of performances was analysed using a linear regression model. Results Two hundred and fifteen horses met the inclusion criteria. There was no difference in either the number of performances or performance score between horses categorised as affected with DOD lesions (independent of joint location) compared with controls. Significantly lower numbers of performances were recorded for horses with osteochondral fragments (OCD) located at the dorsal aspect of the sagittal ridge of the metacarpo/metatarsophalangeal bone. No significant difference was found between horses affected with DOD lesions of the tarsocrural joint and controls. Horses with osteochondrosis of the lateral trochlear ridge of the femur had both significantly lower performance scores and numbers of performances compared with controls. Conclusion This study demonstrated that specific DOD location and site within the joint have an influence on performance. Osteochondral fragments in the femoropatellar and at the dorsal aspect of the sagittal ridge of the metacarpo/metatarsophalangeal joint resulted in lowered performance. Fragmentation in the tarsocrural joint had no influence on performance. Potential relevance The future athletic performance of Warmblood jumping horses may be limited as a result of OCD in the femoropatellar joint and to a certain extent the metacarpo/metatarsophalangeal joint.